Visualizing the 3D structure of medical objects based on 2D data - Stylianou, Georgios; Lanitis, Andreas (My University, 2009)
3D imaging allows the detailed visualization of medical structures that can be very important in the process of treating patients. In this paper we describe a method for generating 3D models representing medical structures, using data derived from a single image showing a single cross-section of an object. The proposed method utilizes a 3D deformable model that is allowed to deform in order to approximate the shape of a medical structure as seen in a single cross-section, allowing in this way the estimation of the complete 3D structure of the object. Experimental results using synthetic data prove the potential of this approach in generating 3D pelvis models.
Keywords: Three-dimensional test of visualization skills; Three-dimensional imaging in medicine